Long-term stability of N-heterocyclic carbene (NHC) functionalized organic electrochemical transistor (OECT) for biosensing applications - Fan, Jiaxin; Kang, Seongdae; Gupta, Manisha (Frontiers in Sensors, 2024)
The increasing demand for the rapid identification of various pathogens and disease biomarkers makes it essential to develop selective and reliable biosensors. The three basic components of a biosensor are: (i) the bioreceptor that binds to the target analyte, (ii) the transducer that converts the signal, and (iii) a signal processing circuit. Integrating the biorecognition elements onto the transducer surface is a critical step that governs the selectivity and reliability of biosensors. Here, we present a novel approach for functionalizing aerosol jet-printed organic electrochemical transistors (OECTs) for biosensing applications. Our design utilizes a printed Au gate modified with N-heterocyclic carbene (NHC) linkers for biofunctionalization. NHC was selected due to its excellent stability and high binding affinity with transition metals, facilitating a robust biofunctionalization mechanism. Utilizing the NHC-Au surfaces, we developed OECT-based biosensors that successfully detected the biotin-streptavidin (biotin-SA) binding events as threshold voltage shift (ΔVT) of 193 ± 64 mV, which is approximately three-fold of that for bovine serum albumin (BSA) (62 ± 41 mV), indicating the NHC functionalized OECT-based biosensor is selective towards the target analyte. In addition, the NHC-Au electrode and the printed OECT both remained functional after 24 months of storage at room temperature, with comparable performances (ΔVT = 161 ± 30 mV for SA binding) as the freshly prepared ones, demonstrating outstanding long-term stability. To the best of our knowledge, this is the first study combining NHC and OECT for biosensing and showcasing 24-month long-term stability. Given the versatility of NHCs in forming highly stable covalent bonds with most transition metals, this study is an important demonstration of their application in bioelectronics. Thus, we have shown a prominent biosensor development technology based on carbenes and organic electronics, which can be adapted to various biomolecule detection and biomedical applications. The exceptional stability of the printed OECTs and NHC functionalized gate highlights their potential for long-term biosensing applications, paving the way for reliable bioelectronics.